2005
DOI: 10.1200/jco.2005.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Radiotherapy in Patients With Relapsed and Refractory Hodgkin’s Lymphoma: A Retrospective Analysis From the German Hodgkin Lymphoma Study Group

Abstract: SRT offers an effective treatment for selected subsets of patients with relapsed or refractory HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 25 publications
2
71
0
11
Order By: Relevance
“…Indeed, the proportion of patients achieving long-term disease control after RT alone is too low. 36 The expert panel recognizes two potential indications of RT (in addition to palliation of incurable HL). Firstly, TBI can be included in the conditioning regimen prior to ASCT for patients at high risk of relapse and who have not been previously irradiated (see below).…”
Section: Radiotherapymentioning
confidence: 99%
“…Indeed, the proportion of patients achieving long-term disease control after RT alone is too low. 36 The expert panel recognizes two potential indications of RT (in addition to palliation of incurable HL). Firstly, TBI can be included in the conditioning regimen prior to ASCT for patients at high risk of relapse and who have not been previously irradiated (see below).…”
Section: Radiotherapymentioning
confidence: 99%
“…In 2005, Josting et al reported the most comprehensive series of salvage radiotherapy alone in 100 patients with primary progressive or relapsed HL. 38 With a median observation time of 52 months, 5-year FF2F and OS for all patients were 28% and 51%, respectively, and for patients with limited stage at progression/relapse, 22% and 55%, respectively.…”
Section: Graft-versus-lymphomamentioning
confidence: 89%
“…The presence of B symptoms, advanced stage (III/IV) at relapse, Karnofsky of < 90% were identified as poor prognostic factors for those patients (Josting, Nogova et al 2005).…”
Section: Role Of Radiotherapy For Rr-hlmentioning
confidence: 99%